Indonesia’s Efforts in Supporting ASEAN Digital Economy by Expanding the Use of QRIS in Southeast Asia - Azhar Rifdahita Maitsa; Azmawati Dian (SHS Web of Conferences)
Through the G20 forum, Indonesia raised the issue of digital transformation and collaborated with four ASEAN countries. Indonesia is also taking advantage of ASEAN Digital Economy Framework Agreement (DEFA) formation by advocating the interoperability of digital payment systems in ASEAN. This research aims to find out what efforts Indonesia has undertaken to support the realization of ASEAN’s digital economy, focusing from the initial approval of the Local Currency Settlement (LCS) which was approved by Indonesia, Malaysia, Thailand, and Philippines in 2016 until Singapore’s joining the Local Currency Transaction (LTC) framework in 2022. The study used a qualitative research method. The data used is secondary data originating from journals, documents, books, and official websites that are able to support research. The findings reveal that Indonesia’s efforts in supporting ASEAN’s digital economy are carried out by advocating the realization of interoperability in the payment system conducted by Indonesia through cooperation in using QRIS digital payments through the Local Currency Transaction (LCT) framework.